EFEK BEKERJA DALAM JARAK DEKAT TERHADAP KEJADIAN MIOPIA - Saminan Saminan (Jurnal Kedokteran Syiah Kuala, 2013)
Abstrak. Beraktivitas dalam jarak dekat merupakan salah satu faktor resiko (efek) terjadinya miopia, semakin lama seseorang memfokuskan penglihatannya untuk melihat dekat semakin lama pula mata seseorang melakukan akomodasi, sehingga lama kelamaan mata akan lelah dan kondisi ini akan memicu pengaburan di retina dan mata menjadi tidak fokus. Miopia adalah suatu bentuk kelainan refraksi dimana sinar sejajar yang datang dari jarak tak terhingga oleh mata yang dalam keadaan tidak berakomodasi dibiaskan pada satu titik didepan retina, penglihatan jauh kabur, maka miopia merupakan penyebab utama gangguan penglihatan. Abstract. Eye is one of the human sensory organs that has the function to look. Someone’s vision is really determined by a light refraction inside the eyes, a vision media consisting of cornea, eye liquid, lens, glass lens and length of eye-ball. Refraction anomaly is one of the blindness causes in the world. Refraction anomaly is a ray refraction on eyes so that the ray is not focused on the retina or fovea, but in the front of or behind the fovea and perhaps it is not located on one focus point; if there is a light refraction anomaly inside the eyes, the observed objects are less clear (sightedness) caused by a light point that is not precised in retina (a light which is not focused in the retina), there are three types of a refraction anomaly, myopia, hyperopia, and astigmatism.